Relación Entre Los Niveles Motivacionales Y La Autoeficacia En Estudiantes De Instrumentos De Cuerda Frotada De Nivel Superior - Alzugaray, Francisco Javier Zarza (European Scientific Journal, ESJ, 2018)
Motivation is one of the most important aspects in the development of a career of learning, even more so if one fits in a musical studies in which motivational levels must be sustained for many years. In this sense, the study of the motivation of musical achievement from the motivational theory of Weiner (2000) and its possible relation with the general self-efficacy described by Bandura (1986) is key to understanding both the formative process of the students and the possible ones pedagogical improvements to include in the Spanish educational system. Significant relationships have been found between the different motivational factors and self-efficacy. In the same way, the motivational factors related to the specific areas present a good explanatory capacity of self-perceived self-efficacy by the students. It is necessary to expand to other psychological constructs for a better understanding of the motivational event in higher musical studies.